Koncentrace a ziskovost na bankovním trhu České Republiky - Černohorský, Jan (Univerzita Pardubice, 2015)
The aim of this paper is to assess the degree of concentration in the Czech banking sector and especially its relationship to profitability in the market. The paper is based on contemporary scientific knowledge based on literature research. There is calculated Herfindahl-Hirschman index of banking market in the Czech Republic in the years 2003-2012. The calculation of concentration is made for three variables - total assets, receivables from clients and deposits from clients. Subsequently, these values are compared with the development of profits in the Czech banking sector using correlation and regression analysis. Necessary tests for normality, autocorrelation and homoscedasticity are conducted before performing correlation and regression analyses. We can conclude that in the case of the Czech Republic, there is an inverse relationship between the degree of concentration and the size of the profits of the banking sector, which is not the standard output of previous studies. The results can be beneficial both to further scientific research and findings, as well as for practical pricing policy of banks, and of course for regulating activity of central banks in context to the licensing of banks.
The concentration and profitability in the Czech banking system
Keywords: bank; banking market; concentration; profitability; G21; C20